PENGARUH FLIPBOOK GERBANG LOGIKA DENGAN MENGGUNAKAN LIVEWIRE TERHADAP KEMAMPUAN BERPIKIR LOGIS MAHASISWA TEKNIK INFORMATIKA - Prasetyono, Rizki Noor; Sigitta Hariyono, Rito Cipta (Universitas Ivet, 2019)
The purpose of the research to explain how the effect of the use of logic gates flipbook using livewire against logical thinking ability of students. The research subjects were informatics engineering students who took digital circuit courses in semester 6 of 2018/2019. The research design was pre-experimental design with one group pretest-posttest type. From the results of simple regression data using SPSS that is obtained p Value Sig. 0,000 <0,05, which means that the use of flipbook logic gates using livewire has an effect on the ability to think logically in informatics engineering students. The percentage 64.5% of logical thinking ability is influenced by the use of flipbook material for livewire logic gate assistance. The simple regression equation as follows Y = = -81,776 + 18,503x, that?s means the flipbook using livewire in logical gate material has a positive influence on students' logical thinking abilities.